Human T-cell leukemia virus type 1 (HTLV-1) tax requires CADM1/TSLC1 for inactivation of the NF-κB inhibitor A20 and constitutive NF-κB signaling. - Rajeshree Pujari; Richard Hunte; Remy Thomas; Louise van der Weyden; Dan Rauch; Lee Ratner; Jennifer K Nyborg; Juan Carlos Ramos; Yoshimi Takai; Noula Shembade (PLoS Pathogens, 2015)
Persistent activation of NF-κB by the Human T-cell leukemia virus type 1 (HTLV-1) oncoprotein, Tax, is vital for the development and pathogenesis of adult T-cell leukemia (ATL) and HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). K63-linked polyubiquitinated Tax activates the IKK complex in the plasma membrane-associated lipid raft microdomain. Tax also interacts with TAX1BP1 to inactivate the NF-κB negative regulatory ubiquitin-editing A20 enzyme complex. However, the molecular mechanisms of Tax-mediated IKK activation and A20 protein complex inactivation are poorly understood. Here, we demonstrated that membrane associated CADM1 (Cell adhesion molecule1) recruits Ubc13 to Tax, causing K63-linked polyubiquitination of Tax, and IKK complex activation in the membrane lipid raft. The c-terminal cytoplasmic tail containing PDZ binding motif of CADM1 is critical for Tax to maintain persistent NF-κB activation. Finally, Tax failed to inactivate the NF-κB negative regulator ubiquitin-editing enzyme A20 complex, and activate the IKK complex in the lipid raft in absence of CADM1. Our results thus indicate that CADM1 functions as a critical scaffold molecule for Tax and Ubc13 to form a cellular complex with NEMO, TAX1BP1 and NRP, to activate the IKK complex in the plasma membrane-associated lipid rafts, to inactivate NF-κB negative regulators, and maintain persistent NF-κB activation in HTLV-1 infected cells.